Invisible forces: How shame and guilt affect L2 achievement through regulating L2 anxiety and enjoyment - Teimouri, Yasser (Studies in Second Language Learning and Teaching, 2025)
Emotions play a crucial role in second and foreign language learning as extensive research in second language acquisition (SLA) has documented the influence of both positive and negative emotions on second and foreign language (L2) learners’ motivation, performance, and L2 attainment. Although language anxiety and enjoyment have garnered particular attention from scholars in the domain of L2 learning, their links with other emotions – more specifically, shame and guilt – remain underexplored. In other words, how L2 learners’ proneness to shame and guilt act as key determiners of their L2 anxiety and enjoyment experiences remains largely unexplored. As such, two separate studies investigated how shame-proneness and guilt-proneness influence L2 achievement by regulating L2 anxiety and enjoyment. In Study 1, a sample of 327 English major university students, and in Study 2, a total of 256 undergraduates from English and non-English majors were recruited. The initial correlational analyses in both studies revealed a strong, positive relationship between shame-proneness and anxiety but a modest, negative correlation between shame-proneness and L2 enjoyment. Conversely, guilt-proneness had a modest, positive correlation with L2 enjoyment and no meaningful relationship with L2 anxiety. Path analyses exhibited that shame-proneness reduced L2 achievement of the students mainly by increasing their L2 anxiety and suppressing L2 joy, whereas guilt-proneness enhanced L2 achievement by boosting L2 enjoyment. The theoretical and pedagogical implications of the findings will be discussed in detail with respect to the contexts of the studies.